NYERI KEPALA PASCATRAUMA: TELAAH EPIDEMIOLOGI DAN PATOFISIOLOGI - Setyaningsih, Indarwati; Kurniandari, Nindriya; Habibi, Muhammad Najmi; Sejahtera, Desin Pambudi (PERDOSNI, 2025)
Post-traumatic headache (PTH) is one of the most common complications following mild traumatic brain injury (TBI). Its clinical presentation often resembles primary headache disorders, such as migraine or tension-type headache; however, it possesses a more complex and multifactorial pathophysiological basis. This article aims to review the epidemiological aspects and pathophysiological mechanisms of PTH based on recent literature. Globally, more than 69 million individuals experience TBI each year, and up to two-thirds of patients with mild TBI are reported to develop PTH. While most cases are transient, approximately 15–25% progress to persistent PTH. The pathogenesis of PTH involves interactions among structural damage, neurometabolic dysfunction, and neuroinflammatory processes that trigger activation of the trigeminovascular system and both peripheral and central sensitization. Cervical factors, hyperadrenergic mechanisms, and disturbances in the descending pain modulatory system further exacerbate symptoms. Advanced neuroimaging studies such as diffusion tensor imaging (DTI), Voxel-based morphometry (VBM), and magnetic resonance spectroscopy (MRS) provide supporting evidence of axonal injury, cortical thinning, and neuronal metabolic abnormalities associated with symptom persistence. A deeper understanding of the interaction among structural, metabolic, and inflammatory dysfunctions may serve as the foundation for developing more effective diagnostic and therapeutic strategies to improve patient’s clinical outcome. Keywords: post-traumatic headache, traumatic brain injury, neuroinflammation, central sensitization, peripheral sensitization